PENGARUH PENGADAAN BAHAN MAKANAN UNTUK OPERASIONAL KITCHEN TERHADAP KINERJA PURCHASING DI HOTEL ALILA SOLO - I Gusti Ayu Agung; Katrin, Yolanda (STABN Raden Wijaya Wonogiri, 2023)
ABSTRACT This research is a descriptive qualitative research. The research subject in this research is purchasing Alila Solo Hotel. Methods of data collection in this study using observation, interviews, literature and documentation. This study aims to find out how the procurement of kitchen food ingredients at the Alila Hotel Solo and how the influence of the procurement of kitchen food ingredients on purchasing performance at the Alila Solo Hotel. The results showed that the procurement of kitchen food ingredients at the Alila Solo Hotel was running properly. Starting from purchase requests, selecting suppliers, placing orders and receiving goods has been done correctly. However, there are obstacles when looking for seasonal food ingredients, when sudden requests occur, discrepancies in delivery by suppliers and order delays. Given these constraints, solutions that can be taken are replacing food ingredients or looking for similar food ingredients, returning food ingredients that are not suitable and good communication is needed between purchasing and the kitchen to avoid miscommunication. The influence of the procurement of kitchen food ingredients on purchasing performance in this study uses performance indicators according to Robbins (2016: 260), namely work quality, work quantity and timeliness. All show that the procurement of food ingredients shows a good influence on purchasing performance at the Alila Solo Hotel. If the procurement of food ingredients in the kitchen goes well, good purchasing performance will also be created. Keywords: Food Procurement, Performance, Purchasing